OS ANGLICISMOS NA ESCRITA DIGITAL E O PROCESSO DE INOVAÇÃO LEXICAL NO PORTUGUÊS BRASILEIRO - PENHA, Alba Catarina Gama Costa (2021)
Linguistic searches show convergent results regarding the importance of the study of the lexicon, which, of course, changes to meet the communicative needs of the speakers. In this regard, considering the multiple possibilities that the language offers us, it is also possible to think of a significant change in the lexicon of the online language. The present work, therefore, aims to investigate, in digital writing, words and / or expressions from English, as well as the processes of lexical creation and incorporation in Brazilian Portuguese. Our starting point was the following guiding question: How do users of the social network Instagram employ anglicisms in the lexical innovation process in Brazilian Portuguese? To answer the guiding question, we resorted mainly to theoretical works on derivational morphology, lexical neology and digital writing, with emphasis on authors such as: Alves (1984, 1994, 2004), Sandmann (1996), Biderman (2001), Isquerdo (2001, 2004, 2007), Basílio (2011), Correia e Almeida (2012) Gonçalves (2012), Spadoro (2013), Shepherd and Saliés (2013), Barton and Lee (2015), among others who discuss linguistics, derivational morphology, lexicology, lexical neology, foreign language, online language, categories of fundamental importance for the unveiling of the phenomenon under our investigation. The methodological procedures are of a qualitative basis and are based on Phenomenology. For data collection, we opted for the construction of a corpus consisting of texts / comments captured from Instagram profiles with more than one million followers. The selected profiles address the following themes: fashion, entertainment and politics. Among the texts / comments of the corpus that we built, we selected only 15 (fifteen) for analysis and these texts / comments are being identified as Descriptions of the research subjects. The data were analyzed in the light of the fundamentals of Perception Phenomenology (MERLEAU-PONTY, 1996), with the researcher experiencing two moments: that of ideographic analysis and that of nomothetic analysis. In this process, the following categories of analysis emerged: adoption of anglicisms, adaptation of anglicisms and innovative neological creation. The analyzed data reveal the following results: there are anglicisms that do not go through any process of adaptation to Portuguese and there are anglicisms adapted through two levels: semantic and morphological. We found that hashtags function as a lexical morpheme and allow the creation of hybrid composite words and that digital textual genres contribute to the occurrence of anglicisms in the interactions carried out on Instagram, since they are hybrid forms of communication. Based on the understanding / interpretation that the reflection attitude provided us about our research object, we suggest new studies on the lexical innovation process in Brazilian Portuguese, considering the peculiarities of interaction / communication mediated by the writing practices developed in the social networks of the web .